Pemberian Pelet dengan Ukuran Berbeda terhadap Pertumbuhan Kepiting Bakau (Scylla serrata Forsskål, 1775) - Aditya, Bagus Pitra; Sunaryo, Sunaryo; Djunaedi, Ali (977-2407769)
Mud crab (S. serrata Forsskål, 1775) is one of the fisheries resources that has high economic value and potential to be cultivated. This study examines provision pellets of different sizes, adapted to the mangrove crab eating patterns. The purpose of this study is investigated the effect of different sizes pellets for the growth of mud crab (S. serrata Forsskål, 1775). This research was conducted at the Laboratory of Coastal Area Development (LPWP), UNDIP, Faculty of Fisheries and Marine Science, University of Diponegoro, Jepara, for 35 days, in October-November 2011. The research method in this study was used experimental laboratory with completely randomized design (CRD) with 3 treatments and 10 replications in each treatment, ie: treatment A (Ø pellets + 10 mm), treatment B (Ø pellets + 5 mm) and treatment C (Ø pellets + 1 mm). Initial weight of mud crab test is 50-55 g and have male gender. Growth of mud crab can be seen from the observation from SGR and supported by some other data, ie: the amount of feed intake, FCR, PER, the amount of energy consumption in feed and water quality parameters. These results indicate that administration of treatment different size pellets effect is very significant (p<0,01) on SGR, FCR, PER. SGR data suggest that on average in treatment A (5,42+0,64) reached the highest value, but not significantly different (p>0,05) with treatment B (5,17+0,52), where’s treatment C (4,02+0,51) reached the lowest value. FCR data show that, in treatment A (5,21+1,12) reached the lowest value, but not significantly different (p>0,05) with treatment B (5,42+1,15), while treatment C (7,16+1,55) reached the lowest value. PER data showed that, in treatment A (0,62+0,13) reached the highest value, but not significantly different (p>0,05) with treatment B (0,60+0,13), while treatment C (0,46+0,11) reached the lowest value.